PENGARUH DOSIS PUPUK KANDANG KAMBING DAN NPK 16:16:16 TERHADAP PERTUMBUHAN DAN KUALITAS JAMBU BIJI KRISTAL (Psidium guajava L.) PADA MUSIM PENGHUJAN - Ariya Listari; Supanjani Supanjani; Sumardi Sumardi; Widodo Widodo; Djamilah Djamilah (Program Studi Ilmu Tanah Fakultas Pertanian UNIB, 2019)
ABSTRACT[THE EFFECT OF GOAT MANURES AND NPK 16:16:16 FERTILIZER ON THE GROWTH OF SEEDLESS GUAVA CROPS AND QUALITY OF ITS FRUIT (Psidium guajava L) AT RAINY SEASONS OF INDONESIA]. Guava var. Crystal, known as seedless guava, is one of the most popular guava in Indonesia. Compated to other guavas, seedless guava has softer texture, tastes sweeter, and has less seeds. This experiment was carried out from September 2017 to February 2018 at Harapan Makmur village, Pondok Kubang regency, and Central Bengkulu district. The objective of this experiment was to evaluate the effect of goat manures and NPK 16:16:16 fertilizers on the growth of guava crops and the quality of its fruits. The experiment was arranged in randomized complete block design (2 factors, 5 replications). The first factor tested was the dose of goat manures, consisting of 3 levels: 0, 9, and 18 kg/plant. The second factor tested was the dose of NPK 16:16:16 fertilizers, consisting of 3 levels: 0, 0,25, and 0.5 kg/plant. The results showed that goat manures significantly affected the diameter and number of branches. In addition, the dose of NPK significantly affected the diameter of branches, degree of leaf greenness, number of flower, and number of aborted flowers. Finally, the interaction between goat manures and NPK manures did not significantly affect all variables measured, except for leaf areas.